RACISM IN THE LAST DECADE OF HOLLYWOOD COMEDY MOVIES - Thiska Septa Maiza; Ida Rochani Adi (Universitas Gadjah Mada, 2019)
The United States is considered to have entered the post-racial era in the 21st century, where racial preference, discrimination, and prejudice towards minorities, such as African Americans, are supposed to no longer exist. As one of the media that reflected American society, Hollywood movies tried to eliminate the discussion on race and racism. It can be seen in Hollywood movies that begin to eliminate the negative images and stereotypes of African Americans. However, it does not mean that racism vanished from the Hollywood movie industry, especially in comedy movies. Comedy movies are one of the genresthat often involve African-American actors and actresses. Their stereotypes are also commonly used to make humor in the narrative. Therefore, this genre is closely related to racism. However, comedy movies in the last decade, such as Evan Almighty (2007), Wild Hogs (2007), Meet Dave (2008), The Maiden Heist (2009), Last Vegas (2013), Someone Marry Barry (2014), and Going in Style (2017), are not showing any racism on the surface. By using Interdisciplinary as the approach, this research attempts to see how Hollywood presents racism in comedy movies, especially in the last decade. The representation theory is employed to interpret the images, scenes, and dialogues from seven selected comedy movies concerning racism. Meanwhile, the theory of humor is used to find out how racism makes humor occur through African-American characters. The finding of this research indicates that negative images and stereotypes of African Americans are still sustained in Hollywood movies. These depictions are shown covertly. Meanwhile, overt racism indicates that the African American characters are used to make humor occur in comedy movies.Keywords: African American; comedy; Hollywood; humor; racism; representation